Dissemination of an Online Theory-Based Intervention to Improve Gluten-Free Diet Adherence in Coeliac Disease: the Relationship Between Acceptability, Effectiveness, and Attrition - Sainsbury, Kirby; Mullan, Barbara; Sharpe, L. (Springer New York LLC, 2015)
Background: Both acceptability and behaviour change data provide important information about the likelihood of success of an intervention when disseminated outside the research context. Despite this, few studies have combined such data for use in ongoing intervention development. Purpose: To assess the acceptability and feasibility of an online intervention to improve gluten-free diet (GFD) adherence in coeliac disease, and to examine the relationships with participant characteristics, attrition, and effectiveness to inform ongoing intervention developments to ultimately reduce attrition and improve the reach and effectiveness of the programme. Methods: All participants completed measures of GFD adherence, theory of planned behaviour variables, psychological symptoms, and demographic and disease characteristics. Acceptability and feasibility ratings were obtained at the conclusion of each of the six intervention modules. Chi-square analyses were used to examine differences between completers and non-completers, and Spearman’s correlations were used to determine the relationships between participant characteristics, effectiveness, and acceptability and feasibility. Results: Participants who rated the early modules less favourably were more likely to drop-out of the intervention. Acceptability and feasibility ratings were also associated with the presence of psychological symptoms, use of adaptive coping strategies, GFD duration, and attitude change. Conclusions: The findings suggest that changes to the structure and implementation of the intervention may be useful in minimising attrition and maximising effectiveness for future dissemination in a wider coeliac disease population.